Adsorption of Heavy Metal Ions on Pomegranate () Peel: Removal and Recovery of Cr(VI) Ions from a Multi-metal Ion System - Rifaqat A.K. Rao; Fouzia Rehman (Adsorption Science & Technology)
The fruit peel of pomegranate ( Punica granatum ) exhibits a high affinity for Cu(II), Ni(II), Cd(II) and Zn(II) ions. The maximum adsorption observed was that of Cu(II) ions, followed by Zn(II), Cd(II), Ni(II) and Cr(VI) ions. The adsorption of Cu(II) ions was dependent on the initial Cu(II) ion concentration, pH, adsorbent dose, temperature and contact time. The adsorption isotherms could be described by the Langmuir and Freundlich equations. Application of the χ 2 -test indicated that both these models were best obeyed at 20 °C. Thermodynamic parameters such as ΔH 0 , ΔS 0 and ΔG 0 were evaluated, the adsorption process being endothermic and spontaneous in nature. The value of the mean free energy indicated that the adsorption process was chemical in nature. Kinetic data showed that the pseudo-second-order model provided the best fit for the experimental data. Attempts were made using batch and column methods to desorb Cu(II), Ni(II), Zn(II), Cd(II) and Cr(VI) ions from synthetic wastewater as well as from wastewater derived from electroplating activities. The breakthrough capacities of Cu(II), Ni(II), Zn(II), Cd(II) and Cr(VI) ions were 6, 2, 2, 2 and 0 mg/g, respectively, when a mixture of these metal ions was treated. The adsorbent was utilized to recover Cr(VI) ions from electroplating wastewater.